Who is killing the tiger Panthera tigris and why?. Issue 1 (28th October 2016) - Saif, Samia; Tuihedur Rahman, H. M.; MacMillan, Douglas Craig
Abstract: We investigated the range of people involved in killing tigers Panthera tigris in the Bangladesh Sundarbans, their motives and methods, and their links to the commercial trade. Using snowball sampling we conducted 141 qualitative interviews with local people. We identified five categories (village residents, poachers, shikaris, trappers and pirates), each with different motives, methods and networks. Village residents kill tigers predominantly for safety, whereas others kill in the forest professionally or opportunistically. Poachers kill tigers for money, but for others the motives are more complex. The motives of local hunters are multifaceted, encompassing excitement, profit, and esteem and status arising from providing tiger parts for local medicine. Pirates kill tigers for profit and safety but also as a protection service to the community. The emerging international trade in tiger bones, introduced to the area by non-local Bangladeshi traders, provides opportunities to sell tiger parts in the commercial trade and is a motive for tiger killing across all groups.